Al Muhajiroun: a case study in contemporary Islamic activism - Weeks, Douglas (Palgrave Macmillan, 2020)
1. Researching the Activists: Understanding Methods, Data, and Approaches -- 2. The Vanguards of Radicalism in the UK -- 3: Al Muhajiroun: The Early Days (1996-2004) -- 4. The Ideology of Al Muhajiroun -- 5. The Post Al Muhajiroun Years (2005-2014): Proscription and Other Means of Deterrence -- 6. The Impacts of the Islamic State and Strategies of Control -- 7. Comparing Ideologies: Al Muhajiroun, Al Qaeda, and Islamic State -- 8. Understanding and Managing the Threat -- 9. Conclusion: Summing up the Activists.